Effect of synthesis routes on the properties and bactericidal activity of cryogels incorporated with silver nanoparticles1. Issue 55 (17th June 2015) - Loo, Siew-Leng; Krantz, William B.; Fane, Anthony G.; Hu, Xiao; Lim, Teik-Thye
<x xml:space="preserve">Abstract</x> AgNPs-incorporated cryogels prepared via three synthesis routes were explored as antibacterial sorbents for water disinfection.